Robust and Broadband Graphene Surface Plasmon Waveguide Coupler via Quantum Control - Chen, Yun; Huang, Wei; Ooi, Kelvin J. A.; Zhang, Wentao (Frontiers in Physics, 2022)
In this paper, a novel graphene sub-wavelength waveguide coupler is designed based on quantum control theory. Compared with metal surface plasmon-polaritons (SPPs), graphene surface plasmon-polaritons (GSPPs) have a smaller SPP wavelength and tunable properties. The dielectric load graphene plasmon waveguide (DLGPW) is used for design to avoid the influence of the edge shape of the graphene nanoribbons on the waveguide mode. The coupling coefficient between the waveguides is calculated by using the coupled-mode theory (CMT). Due to the subwavelength properties of graphene surface plasmons (GSP) and the robustness of the quantum control technique, our device is more compact and robust against perturbations of geometrical parameters under the premise of high transmission efficiency. The device we design also has broadband characteristics, ranging from 30THz to 40THz, with high transmission efficiency when considering the transmission loss. We believe that our device will significantly contribute to integrated optics and photo-communication.